Contrasting effects of ascorbate and iron on the pulmonary vascular response to hypoxia in humans - Talbot, Nick P. (Physiol Rep, 2014)
Hypoxia causes an increase in pulmonary artery pressure. Gene expression controlled by the hypoxia‐inducible factor (HIF) family of transcription factors plays an important role in the underlying pulmonary vascular responses. The hydroxylase enzymes that regulate HIF are highly sensitive to varying iron availability, and iron status modifies the pulmonary vascular response to hypoxia, possibly through its effects on HIF. Ascorbate (vitamin C) affects HIF hydroxylation in a similar manner to iron and may therefore have similar pulmonary effects. This study investigated the possible contribution of ascorbate availability to hypoxic pulmonary vasoconstriction in humans. Seven healthy volunteers undertook a randomized, controlled, double‐blind, crossover protocol which studied the effects of high‐dose intravenous ascorbic acid (total 6 g) on the pulmonary vascular response to 5 h of sustained hypoxia. Systolic pulmonary artery pressure (SPAP) was assessed during hypoxia by Doppler echocardiography. Results were compared with corresponding data from a similar study investigating the effect of intravenous iron, in which SPAP was measured in seven healthy volunteers during 8 h of sustained hypoxia. Consistent with other studies, iron supplementation profoundly inhibited hypoxic pulmonary vasoconstriction (P < 0.001). In contrast, supraphysiological supplementation of ascorbate did not affect the increase in pulmonary artery pressure induced by several hours of hypoxia (P = 0.61). We conclude that ascorbate does not interact with hypoxia and the pulmonary circulation in the same manner as iron. Whether the effects of iron are HIF‐mediated remains unknown, and the extent to which ascorbate contributes to HIF hydroxylation in vivo is also unclear.